Ultra‐Rapid Removal of Pb(II) Ions by a Nano‐MoS2 Decorated Graphene Aided by the Unique Combination of Affinity and Electrochemistry (Adv. Sustainable Syst. 7/2022). (22nd July 2022) - Arya Nair, J. S.; Saisree, S.; Sandhya, K. Y.
Abstract : Water Purification The image representing article 2200039 by K. Y. Sandhya and co‐workers is a symbolic depiction of a partially reduced graphene oxide‐molybdenum disulfide nanocomposite (prGO‐MoS2 ) for the ultra‐rapid and selective removal of Pb(II) ions from contaminated water within ≤3 minutes in the presence of other ions, due to the selective interaction and the electrochemistry between the Pb(II) and S 2− and oxygen moieties of prGO‐MoS2 .